A Case of a Metal Foreign Object Remaining in the Maxillary Bone for an Extended Period: A Case Report - Koichi Kadoya; Yuki Kunisada; Kyoichi Obata; Hiroaki Takakura; Tatsuo Ogawa; Soichiro Ibaragi (Clinical Case Reports)
ABSTRACT We report a rare case in which a metallic foreign body remained undetected in a patient's maxilla for nearly 40 years after a childhood bicycle accident. Despite the accident, the implant remained in place without causing infection due to the lack of imaging studies at the time. The metal was accidentally discovered during a routine dental imaging examination 40 years later and subsequently surgically removed. This case highlights the importance of comprehensive imaging and the dangers of overlooking foreign bodies, especially in the vulnerable head and neck region. The patient, 53 years old at the time of discovery, presented to the dentist due to discomfort in the palate and nasal cavity. During this visit, radiographs were taken and a foreign body was discovered. Surgical removal of the foreign body revealed significant corrosion and surrounding granulation tissue indicative of foreign body granuloma. Elemental analysis of the foreign body confirmed that it was an iron‐based metal, unlike biocompatible materials such as titanium. These findings reinforce the need for close post‐trauma evaluation and follow‐up, especially in cases of pediatric trauma, to avoid the possibility of long‐term complications arising from unnoticed foreign bodies in anatomically significant areas.